Influence of Customer Service on Customer Satisfaction Indonesian Sharia Bank KCP Bengkalis - Kurniatul FilKurniatul Fil Khoirin; Khodijah Ishak; Muhammad Ise Selamat; Uswatul Hasanah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Quality of service is an effort to fulfill needs coupled with consumer desires and the accuracy of the delivery method in order to meet customer expectations and satisfaction. Customer satisfaction is the level of one's feelings after comparing the performance (or results) that he perceives compared to his expectations. This study aims to analyze the quality of customer service on customer satisfaction and examine the effect of customer service quality on customer satisfaction at Bank Syari'ah Indonesia (BSI) Bengkalis Branch. The author uses a quantitative approach with descriptive analysis methods and statistical analysis. The population in this study as many as 6000 customers with the number of samples taken as many as 100 customers. While the data collection tool used is a questionnaire. The results of the research analysis show that the influence of customer service quality on customer satisfaction at Bank Syari'ah Indonesia (BSI) KCP Bengkalis shows a positive and significant effect on Customer Satisfaction with a contribution of 58% and the remaining 42% is influenced by other factors not examined